2021
DOI: 10.1159/000515587
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Cryoglobulinemia Secondary to Hepatitis C in a Patient with HCV RNA (−) Negative in the Serum

Abstract: Hepatitis C virus infection is associated with many extrahepatic manifestations such as mixed cryoglobulinemia (MC). Renal manifestation of HCV infection might present as cryo-positive membranoproliferative glomerulonephritis (MPGN). First-line therapy includes antiviral treatment as the underlying infection leads to formation of immune complexes. After introducing direct-acting antiviral agents (DAAs) cure rates of HCV infection increased. Sustained virologic response (SVR) is defined as the absence of HCV RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It is a product that has a very desirable composition for this category of products, because it contains only 6 ingredients (except meat), and these ingredients are water and spices. The only drawback that couldbe indicated is the presence of glucose, which is not necessary for the production of meat products, but it is a source of simple sugars, and therefore may contribute to the formation of obesity 9 .…”
Section: Preservative (Sodium Nitrite)mentioning
confidence: 99%
“…It is a product that has a very desirable composition for this category of products, because it contains only 6 ingredients (except meat), and these ingredients are water and spices. The only drawback that couldbe indicated is the presence of glucose, which is not necessary for the production of meat products, but it is a source of simple sugars, and therefore may contribute to the formation of obesity 9 .…”
Section: Preservative (Sodium Nitrite)mentioning
confidence: 99%
“…The lag in immunologic and/or clinical response behind the viral clearance may be due to delay in the clearance of cryoglobulins from the circulation after successful antiviral therapy or to the persistence of the RF-producing memory B-cell clones for at least 24 wk[ 90 ]. Occult HCV infection is another possible explanation especially in case of cryoglobulinemic glomerulonephritis[ 91 ]. Abdelhamid et al [ 92 ] suggested that some forms of alteration in the immune system can be responsible for the persistent HCV-related immune disease after viral clearance.…”
Section: Extrahepatic Manifestations Of Chronic Hepatitis C Virus Inf...mentioning
confidence: 99%
“…In MPGN associated with MCV, the developed immune complex deposits in the mesangium, capillaries, and urinary space of glomeruli, which can be manifested as nephrotic and nephritic syndromes[ 91 , 103 , 104 ]. Furthermore, HCV can cause kidney damage through direct cytopathic effect by viral invasion of the renal parenchyma (mesangial, endothelial, and tubular cells of the kidney) and through nephrotoxicity of drugs used for its treatment.…”
Section: Extrahepatic Manifestations Of Chronic Hepatitis C Virus Inf...mentioning
confidence: 99%
“…It was also shown that viral antigen NS3 and HCV particles are present in kidney tissue of seropositive and seronegative patients with glomerulonephritis, being likely the cause of renal injury [69][70][71]. Likewise, occult HCV infection may be a hidden cause of many cases of mixed cryoglobulinemia in patients with no evidence of past or present HCV infection [72,73]. Replicative HCV-RNA strand was found in PBMC of five out of nine patients with mixed cryoglobulinemia who reached SVR after antiviral therapy and remained HCV-RNA negative both in serum and liver tissue.…”
Section: Clinical Consequences Of Ocimentioning
confidence: 99%